2021
DOI: 10.26434/chemrxiv.14661612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local Energy Decomposition Analysis and Molecular Properties of Encapsulated Methane in Fullerene (CH4@C60)

Abstract: Methane has been successfully encapsulated within cages of C<sub>60</sub> fullerene, and it is an appropriate model system to study confinement effects. Its chemistry and physics is also relevant for theoretical model descriptions. Here we provided insights into intermolecular interactions and predicted spectroscopic responses of the CH<sub>4</sub>@C<sub>60</sub> complex and compared with results from other methods and with literature data. Local energy decomposition analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Interaction energies of H2O molecules with Ti [5] and Obr adsorption sites were evaluated with the local energy decomposition analysis (LED). 46 Results indicated that interaction mechanisms involved mainly electrostatics and London dispersion. Whereas the former is expected to dominate because of the permanent dipole moment of the H2O molecule, the extent of the latter was quite surprising.…”
Section: Anatase (101)mentioning
confidence: 99%
“…Interaction energies of H2O molecules with Ti [5] and Obr adsorption sites were evaluated with the local energy decomposition analysis (LED). 46 Results indicated that interaction mechanisms involved mainly electrostatics and London dispersion. Whereas the former is expected to dominate because of the permanent dipole moment of the H2O molecule, the extent of the latter was quite surprising.…”
Section: Anatase (101)mentioning
confidence: 99%
“…Interestingly, by high-energy collisions of ionized fullerene species, harsh conditions of high temperature and pressure, electric arc, or by organic synthesis methods ("molecular surgery"), it is nowadays possible to produce C 60 endohedral complexes with metal ions, noble gases, and small molecules, such as H 2 , N 2 , H 2 O, and CH 4 (the first organic molecule to be encapsulated) [3][4][5][6][7][8]. Such recent achievements in the synthesis of endohedral fullerene complexes have stimulated many experimental and theoretical investigations since the cavity inside fullerenes provides a unique environment for the study of isolated atoms and molecules.…”
Section: And References Therein)mentioning
confidence: 99%